Antiviral activity against the hepatitis C virus (HCV) of 1-indanone thiosemicarbazones and their inclusion complexes with hydroxypropyl-β- cyclodextrin - Glisoni, Romina Julieta (2012)
The hepatitis C virus (HCV) is a major cause of acute and chronic hepatitis in humans. Approximately 5% of the infected people die from cirrhosis or hepatocellular carcinoma. The current standard therapy comprises a combination of pegylated-interferon alpha and ribavirin. Due to the relatively low effectiveness, the prohibitive costs and the extensive side effects of the treatment, an intense research for new direct-acting anti-HCV agents is taking place. Furthermore, NS3 protease inhibitors recently introduced into the market are not effective against all HCV subgenotypes. Thiosemicarbazones (TSCs) have shown antiviral activity against a wide range of DNA and RNA viruses. However, their extremely low aqueous solubility and high self-aggregation tendency often preclude their reliable biological evaluation in vitro. In this work, we investigated and compared for the first time the anti-HCV activity of two 1-indanone TSCs, namely 5,6-dimethoxy-1-indanone TSC and 5,6-dimethoxy-1- indanone N4-allyl TSC, and their inclusion complexes with hydroxypropyl-β- cyclodextrin (HPβ-CD) in Huh-7.5 cells containing the full-length and the subgenomic subgenotype 1b HCV replicon system. Studies of physical stability in culture medium showed that free TSCs precipitated rapidly and formed submicron aggregates. Conversely, TSC complexation with HPβ-CD led to more stable systems with minimal size growth and drug concentration loss. More importantly, both TSCs and their inclusion complexes displayed a potent suppression of the HCV replication in both cell lines with no cytotoxic effects. The mechanism likely involves the inhibition of non-structural proteins of the virus. In addition, findings suggested that the cyclodextrin released the drug to the culture medium over time. This platform could be exploited for the study of the drug toxicity and pharmacokinetics animal models.